Polymer-based ion exchange membrane as well as preparation method and application thereof

By using DMAEMA and MMA in a homogeneous ion exchange membrane for radical polymerization and grafting into brominated polyphenylene ether through the homogeneous ion exchange membrane, the problem of low ion exchange capacity and conductivity of the existing homogeneous ion exchange membrane is solved, and a high ion exchange capacity and conductivity are achieved.

CN119899412AActive Publication Date: 2025-04-29UNIV OF SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510077752.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-29
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing homogeneous ion exchange membranes generally have problems with low ion exchange capacity and conductivity.

Method used

By conducting free radical polymerization of dimethylaminoethyl methacrylate (DMAEMA) and methyl methacrylate (MMA), polymer is generated, and grafted into brominated polyphenylene ether by the Menthiujin reaction, an anion exchange membrane with high ion exchange capacity and conductivity is prepared.

Benefits of technology

The ion exchange capacity and conductivity of the ion exchange membrane have been significantly improved, and it has high social use value and application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899412A_ABST
    Figure CN119899412A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer-based ion exchange membrane as well as a preparation method and application thereof, dimethylaminoethyl methacrylate (DMAEMA) and methyl methacrylate (MMA) in a specific ratio of (1: 3) are taken as raw materials, a high polymer is generated through free radical polymerization reaction, and then the high polymer is grafted into brominated polyphenyl ether through a Michael reaction, so that the polymer-based ion exchange membrane is obtained. Therefore, a series of anion exchange membranes are prepared. The prepared ion exchange membrane has excellent ion exchange capacity, water content, swelling rate and conductivity, and has high social use value and application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical engineering, and in particular to a polymer-based ion exchange membrane and a preparation method and application thereof. Background Art

[0002] Membrane technology has gradually shown its important role and bright prospects in daily life. In particular, as a new separation technology, it has been widely used in gas separation, material separation, water treatment and other processes. Ion exchange membrane, as a branch of membrane materials, has also been widely used in energy and electricity, biopharmaceuticals, sewage reuse and other fields due to its good ion conductivity and strong hydrophilicity.

[0003] Ion exchange membrane is a membrane-like exchange resin with selective permeability and containing active ion exchange groups. It is composed of three parts: fixed groups, mobile ions on the groups and polymer skeletons. Ion exchange membranes can be divided into cation exchange membranes and anion exchange membranes according to the different types of charges, and can also be divided into heterogeneous ion exchange membranes, homogeneous ion exchange membranes and semi-homogeneous ion exchange membranes according to the macroscopic structure of the membrane. Heterogeneous ion exchange membranes are made of adhesives and fine powder ion exchange resins through intensive refining, stretching, hot pressing and other processes. They have two structural states of powdered ion exchange resins with active groups and inert adhesives, forming an uneven and discontinuous chemical structure. Homogeneous ion exchange membranes are made by introducing active groups into polymers with inert supports as carriers, and chemical reactions occur to combine the membrane material with the active groups on the membrane to form a uniform chemical structure, which has the characteristics of low resistance and excellent electrochemical properties. Semi-homogeneous ion exchange membranes introduce active groups into polymers, but they cannot complete chemical bonding, so that the macroscopic structure of the resulting membrane is between heterogeneous and homogeneous ion exchange membranes.

[0004] However, existing homogeneous ion exchange membranes generally have the problem of low ion exchange capacity and conductivity. Summary of the invention

[0005] In order to solve the problems existing in the above-mentioned prior art, the present invention provides a polymer-based ion exchange membrane and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for preparing a polymer-based ion exchange membrane comprises the following steps:

[0008] S1, methyl methacrylate (MMA) and dimethylaminoethyl methacrylate (DMAEMA) are mixed and added into anhydrous ethanol to be fully dissolved, and then azobisisobutyronitrile (AIBN) as an initiator is added, and the mixture is reacted at 60-80° C. for 12-24 hours under an argon environment to obtain a polymer solution;

[0009] S2, the polymer solution obtained in step S1 is subjected to rotary evaporation at 35-55° C., and the obtained viscous polymer is repeatedly purified by dissolving in chloroform and precipitating in n-hexane; the purified polymer is placed in a vacuum drying oven and dried to obtain polymer D1M3;

[0010] S3, adding polymer D1M3 to an organic solvent, stirring until completely dissolved, and obtaining a polymer D1M3 solution with a mass concentration of 5 to 12% for standby use;

[0011] S4, taking the purified brominated polyphenylene ether BPPO and adding it to an organic solvent, stirring until it is completely dissolved, and obtaining a BPPO solution with a mass concentration of 2 to 3% for standby use;

[0012] S5. Add BPPO solution to the polymer D1M3 solution, stir and react for 2 to 3 hours, spread the resulting reaction solution evenly on a glass sheet and dry it, and the formed film is the target ion exchange membrane.

[0013] Preferably, in step S1, the molar ratio of MMA to DMAEMA is 1:3, and the amount of AIBN added is 1% of the total mass of the polymer monomers.

[0014] Preferably, in step S2, the temperature of the vacuum drying oven is controlled to be 50-55°C, and the drying time is 48-50 hours.

[0015] Preferably, the organic solvent in step S3 and step S4 is N-methyl-2-pyrrolidone

[0016] Preferably, in step S4, the degree of bromination of the purified brominated polyphenylene ether is 23%.

[0017] Preferably, in step S5, the volume ratio of the polymer D1M3 solution to the BPPO solution is (0.2-0.75):4. The specific reaction formula of the polymer D1M3 and the brominated polyphenylene ether is as follows: Figure 1 shown.

[0018] Preferably, in step S5, the temperature of the glass sheet is 60-80° C., and the drying time is 3-8 hours.

[0019] The ion exchange membrane prepared by the method of the present invention can be applied to energy and electricity, biopharmaceuticals, sewage reuse and other fields.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0021] The present invention uses dimethylaminoethyl methacrylate (DMAEMA) and methyl methacrylate (MMA) in a specific ratio (1:3) as raw materials to generate a polymer through a free radical polymerization reaction. The polymer is then grafted onto brominated polyphenylene ether through a Menxiu gold reaction to prepare a series of anion exchange membranes. The experimental results in the embodiment show that when the volume ratio of the polymer D1M3 solution to the BPPO solution is 0.75:4, the ion exchange capacity IEC of the obtained anion exchange membrane is 2.5mmol g -1 , water content is 26.9%, swelling ratio is 10.0%, conductivity is 23.5mS cm -1 , has high social use value and application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 is the specific reaction formula of polymer D1M3 and brominated polyphenylene ether;

[0024] Figure 2 Graph showing the anion exchange capacity of the ion exchange membranes prepared in Examples 2-4 of the present invention;

[0025] Figure 3 The moisture content diagram of the ion exchange membrane prepared in Examples 1-4 of the present invention;

[0026] Figure 4 The linear swelling rate diagram of the ion exchange membrane prepared in Examples 1-4 of the present invention;

[0027] Figure 5 The conductivity diagram of the ion exchange membrane prepared in Examples 1-4 of the present invention;

[0028] Figure 6 The infrared spectra of the ion exchange membranes prepared in Examples 1-4 of the present invention;

[0029] Figure 7 Scanning electron microscope images of the ion exchange membranes prepared in Examples 1-4 of the present invention (a. M2 surface morphology; b. M2 cross-sectional morphology; c. M3 surface morphology; d. M3 cross-sectional morphology; e. M4 surface morphology; f. M4 cross-sectional morphology). DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] In this embodiment, the ion exchange membrane is prepared according to the following steps:

[0033] S1. Mix 2.00 mL of methyl methacrylate (MMA) and 6.28 mL of dimethylaminoethyl methacrylate (DMAEMA), add 120.96 mL of anhydrous ethanol to fully dissolve them, then add 1% of azobisisobutyronitrile (AIBN) in the total weight of the polymer monomer, and react at 70° C. for 24 h under an argon environment to obtain a polymer solution.

[0034] S2. The polymer solution obtained in step S1 is subjected to rotary evaporation at 50°C, and the obtained viscous polymer is dissolved in chloroform and repeatedly purified by n-hexane precipitation. The purified polymer is placed in a vacuum drying oven and dried at 50°C for 48 hours to obtain a final product, which is named polymer D1M3.

[0035] S3. Take 4.0680 g of polymer D1M3 and add it into 35.62 mL of N-methyl-2-pyrrolidone. Stir until it is completely dissolved to obtain a polymer D1M3 solution with a mass concentration of 10% for standby use.

[0036] S4. Take 3.0000 g of purified brominated polyphenylene ether (BPPO, degree of bromination 23%) and add it to 26.32 mL of N-methyl-2-pyrrolidone, and stir until it is completely dissolved to obtain a BPPO solution for standby use.

[0037] S5. Add 4.00 mL of BPPO solution to 0 mL of polymer D1M3 solution and stir to react for 2 h. Spread the prepared solution evenly on a glass sheet at 80° C. and dry for 3 h. The formed film is the target ion exchange membrane, named M1.

[0038] Example 2

[0039] In this embodiment, an ion exchange membrane is prepared by the same process as in Embodiment 1, except that the volume of the polymer D1M3 solution in step S5 is 0.25 mL, and the obtained ion exchange membrane is named M2.

[0040] Example 3

[0041] In this embodiment, an ion exchange membrane is prepared by the same process as in Embodiment 1, except that the volume of the polymer D1M3 solution in step S5 is 0.50 mL, and the obtained ion exchange membrane is named M3.

[0042] Example 4

[0043] In this example, an ion exchange membrane was prepared by the same process as in Example 1, except that the volume of the polymer D1M3 solution in step S5 was 0.75 mL, and the obtained ion exchange membrane was named M4.

[0044] The ion exchange membranes prepared in Examples 1-4 were subjected to the following performance characterization tests:

[0045] 1. Ion exchange capacity (IEC)

[0046] Weigh a small amount of membrane sample and place it in a 60℃ oven for 24 hours to maintain constant weight. -1 NaCl solution for 24 h, rinsed with a large amount of deionized water for 24 h, and then soaked in 0.5 mol L -1 Na2SO4 solution for 24 hours, with 0.01 mol -1 LAgNO3 solution is titrated with potassium dichromate as the indicator. The color changes from bright yellow to earthy brown. The volume of AgNO3 consumed is V AgNO3 The mass of the membrane sample after constant weight is recorded as W1. The calculation formula of the anion exchange capacity value is shown in formula (1), where C AgNO3 is the molar concentration of AgNO3:

[0047]

[0048] from Figure 2 It can be seen from the trend that the ion exchange capacity of ion exchange membranes M2, M3 and M4 shows a trend of increasing successively, and the specific order is: IEC M2 (1.2mmol g -1 ) <IEC M3 (1.4mmol g -1 ) <IEC M4 (2.5mmol g -1 ). This is because the tertiary amine group in polymer D1M3 reacts with the BPPO group to generate a quaternary amine group, which carries a positive charge, thus accelerating the transfer of ions. As the amount of polymer D1M3 solution added increases, more quaternary amine groups are generated by grafting, so the ion exchange capacity shows an upward trend.

[0049] 2. Water content (WU) and swelling rate (SR)

[0050] The moisture content refers to the content of intrinsic water combined with active functional groups in the ion exchange membrane; the linear swelling rate refers to the percentage of the volume of the expanded part of the membrane after it is immersed in water to the volume of the original part.

[0051] Cut a 20mm×20mm sample film, place it in a 60℃ oven for 24 hours, and measure the side length L1 and weight W2 of the sample film. Then immerse the film in deionized water for 24 hours, take out the sample film, gently wipe off the water droplets left on the film, press the film to measure the side length L2 and weight W3.

[0052] The calculation formula of water content is shown in formula (2):

[0053]

[0054] The calculation formula of the swelling rate is shown in formula (3):

[0055]

[0056] from Figure 3 It can be seen that the water content of ion exchange membranes M2, M3 and M4 increases in sequence: WU M2 (2.0%) <WU M3 (10.1%) <WU M4 (26.9%). This phenomenon occurs because the tertiary amine group in the polymer D1M3 reacts with the bromomethyl group in the BPPO group to produce a quaternary amine group. The quaternary amine group is hydrophilic. The more polymer D1M3 solution is added, the higher the hydrophilicity of the quaternary amine group and the membrane. As a result, the water content of the ion exchange membrane increases as shown in the figure above.

[0057] from Figure 4 It can be seen that the linear swelling ratios of ion exchange membranes M2, M3 and M4 show an increasing trend. The specific trends are as follows: SR M2 (2.0%) <SR M3 (8.0%) <SR M4 The reason for the sequential increase is that the tertiary amine group and the bromomethyl group react to form a quaternary amine group. The linear swelling rate is related to the hydrophilicity of the membrane, and the hydrophilicity of the membrane is related to the quaternary amine group. Therefore, the increase in the amount of polymer will increase the linear swelling rate of the membrane.

[0058] 3. Hydroxide conductivity

[0059] Hydroxide conductivity is an important indicator for measuring ion exchange membranes, which can well reflect the performance of ion exchange membranes. The Menxiu gold reaction between tertiary amine groups and bromomethyl groups in polymers can produce a large number of active sites for quaternary amine groups, thus enabling rapid conduction with anions.

[0060] A rectangular sample film of 10 mm × 40 mm was cut out with a knife and immersed in 1 mol L -1 The membrane was placed in NaOH solution for 12 hours, then carefully removed and the membrane surface was repeatedly rinsed with deionized water to ensure that the OH on the membrane surface was washed away. - The chemical resistance of the ion exchange membrane rinsed with deionized water under alternating current is measured. The generated membrane resistance is recorded as R, the distance between the electrodes is D, the thickness of the membrane is measured as T, and the width is W.

[0061] OH of the membrane sample - The calculation formula of conductivity (σ) is shown in formula (4):

[0062]

[0063] like Figure 5 It can be seen that the higher the amount of polymer D1M3, the higher the OH - The conductivity of the membrane increases with the increase of the amount of polymer added. This is mainly because the hydrophilicity of the membrane becomes stronger and it can absorb more water molecules. Therefore, the conductivity of hydroxide ions shows an upward trend. The specific increase trend is: σ M1 (1.3mS cm -1 )<σ M2 (2.8mS cm -1 )<σ M3 (18.4mS cm -1 )<σ M4 (23.5mScm -1 ).

[0064] 4. Infrared spectroscopy characterization

[0065] The four films M1, M2, M3, and M4 were dried at 60°C for 24 hours, and the fine powder on the surface was carefully scraped and extracted for infrared spectrum measurement. A small amount of fine powder scraped from each film was mixed with potassium bromide and pressed into a sheet, and finally the infrared spectra of the four films were measured.

[0066] like Figure 6 As shown, the four films were at 1601 cm -1 and 1470cm -1 The skeleton vibration peak of the benzene ring appeared at 2850cm -1 The stretching vibration peak of CH on saturated alkanes appeared at 2920 cm -1 The stretching vibration peak of CH on the benzene ring appeared at 3500 cm -1 There are characteristic peaks at 1680cm, and M2, M3 and M4 are becoming more and more obvious. This is the result of the membrane absorbing water during the test. -1There are strong absorption peaks at M2, M3 and M4, but there is no peak at M1. This is because the quaternary amine groups are produced by the Menxiu gold reaction between the bromomethyl groups in the base film and the tertiary amine groups in the polymer.

[0067] 5. Scanning Electron Microscope (SEM)

[0068] M2, M3 and M4 were dried at 60°C for 24 hours, and then the surface and cross section of the film were cut out and stuck on the sample stage. After uniform gold spraying, SEM measurement was performed. Finally, the surface and cross section of M1, M2, M3 and M4 were photographed, and the final photos were saved. The results are as follows: Figure 7 shown.

[0069] from Figure 7 (a) to Figure 7 (f) The surface and cross-sectional SEM images show that the ion exchange membrane has a dense membrane morphology. Figure 7 (a) Figure 7 (b) Figure 7 (e) and Figure 7 (f) The surface and cross section show that the surface of the film is relatively rough, which is caused by tearing during cutting; Figure 7 (c) and Figure 7 The surface and cross section of (d) are complete and smooth, indicating that the surface and cross section of the membrane are relatively uniform and flat.

[0070] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a polymer-based ion exchange membrane, characterized in that: The following steps are involved: S1, methyl methacrylate MMA and dimethylaminoethyl methacrylate DMAEMA are mixed and added into anhydrous ethanol to be fully dissolved, and then azobisisobutyronitrile AIBN as an initiator is added, and the mixture is reacted at 60-80° C. for 12-24 hours under an argon environment to obtain a polymer solution; S2, the polymer solution obtained in step S1 is subjected to rotary evaporation at 35-55° C., and the obtained viscous polymer is repeatedly purified by dissolving in chloroform and precipitating in n-hexane; the purified polymer is placed in a vacuum drying oven and dried to obtain polymer D1M3; S3, adding polymer D1M3 to an organic solvent, stirring until completely dissolved, and obtaining a polymer D1M3 solution with a mass concentration of 5 to 12% for standby use; S4, taking the purified brominated polyphenylene ether BPPO and adding it to an organic solvent, stirring until it is completely dissolved, and obtaining a BPPO solution with a mass concentration of 2-3% for standby use; S5. Add BPPO solution to the polymer D1M3 solution, stir and react for 2 to 3 hours, spread the resulting reaction solution evenly on a glass sheet and dry it, and the formed film is the target ion exchange membrane.

2. The method for preparing a polymer-based ion exchange membrane according to claim 1, characterized in that: In step S1, the molar ratio of MMA to DMAEMA is 1:3, and the amount of AIBN added is 1% of the total mass of the polymer monomers.

3. The method for preparing a polymer-based ion exchange membrane according to claim 1, characterized in that: In step S2, the temperature of the vacuum drying oven is controlled at 50-55°C, and the drying time is 48-50 hours.

4. The method for preparing a polymer-based ion exchange membrane according to claim 1, characterized in that: The organic solvent in step S3 and step S4 is N-methyl-2-pyrrolidone.

5. The method for preparing a polymer-based ion exchange membrane according to claim 1, characterized in that: In step S4, the degree of bromination of the purified brominated polyphenylene ether is 23%.

6. The method for preparing a polymer-based ion exchange membrane according to claim 1, characterized in that: In step S5, the volume ratio of the polymer D1M3 solution to the BPPO solution is 0.2-0.75:

4.

7. The method for preparing a polymer-based ion exchange membrane according to claim 1, characterized in that: In step S5, the temperature of the glass sheet is 60-80° C., and the drying time is 3-8 hours.

8. A polymer-based ion exchange membrane prepared by the preparation method according to any one of claims 1 to 7.

9. An application of the polymer-based ion exchange membrane according to claim 8, characterized in that: Applied in the fields of energy and electricity, biopharmaceuticals or sewage reuse.

Citation Information

Patent Citations

  • Preparation method of anion exchange membrane

    CN110560181A

  • Preparation method of amphoteric ion exchange membrane based on polymer

    CN115181307A

  • Cross-linked anionic conductive polymer and uses thereof

    KR1020170142420A

  • Cathode active material, preparing method thereof, an Cathode including the same, and Secondary battery including the same

    KR1020220144697A